Combined specular microscopy and Scheimpflug imaging to improve detection of an upcoming allograft rejection after DMEK. Issue 3 (4th September 2019) - Baydoun, Lamis; Bruinsma, Marieke; Santander‐García, Diana; Ham, Lisanne; Oellerich, Silke; Melles, Gerrit R.J.
Abstract: Purpose: To assess whether combined analysis of specular microscopy and Scheimpflug imaging improves detection of an upcoming allograft rejection following Descemet membrane endothelial keratoplasty (DMEK). Methods: Retrospective analysis of 22 eyes that had developed a clinical proven allograft rejection 28 (±22) months (range: 4–84 months) after DMEK. Specular microscopy and Scheimpflug images routinely made after DMEK were retrospectively analysed for changes in endothelial cell morphology (e.g. nuclear activation), cell density (>10%) and pachymetry (>7%), and/or the presence of subclinical keratic precipitates. The same parameters were evaluated for 22 control eyes matched for age, gender and surgery indication. Results: A total of 20/22 eyes (91%) showed detectable changes 0.25–75 months before allograft rejection became clinically manifest: 13/22 (59%) showed both specular microscopy and Scheimpflug imaging changes; 5/22 (23%) only had changes on Scheimpflug imaging; and 2/22 (9%) only had specular microscopy changes. In 18/22 (82%) and 14/22 (64%) eyes, subclinical keratic precipitates and endothelial cell morphology changes could be detected, respectively. A total of 11/22 (50%) eyes concurrently showed a >10% drop in endothelial cell density and 4/22 (18%) a >7% pachymetry increase. Of the control eyes, 7/22 (32%) showed changes with specular microscopy but not with Scheimpflug imaging. Conclusions: Combined analysis of specular microscopy and Scheimpflug imaging may allow recognizing an upcoming allograft rejection in over 90% of eyes and up to 6 years before rejection becomes clinically manifest. Early recognition of eyes at risk may allow for targeted intensified steroid treatment to prevent endothelial cell damage associated with rejection.